Genetic Diversity of Australian Bacillus anthracis Isolates Revealed by Multiple-Locus Variable-Number Tandem Repeat Analysis - Muller, Janine (Microorganisms, 2020)
Outbreaks of anthrax occur sporadically in Australia and most commonly in the “anthrax belt”, a region which extends from southern Queensland through the centre of New South Wales and into northern Victoria. Little is known about the epidemiological links between Bacillus anthracis isolates taken from different outbreaks and the diversity of strains within Australia. We used multiple-locus variable-number tandem repeat analysis employing 25 markers (MLVA25) to genotype 99 B. anthracis isolates from an archival collection of Australian isolates. MLVA25 genotyping revealed eight unique genotypes which clustered within the previously defined A3 genotype of B. anthracis. Genotyping of B. anthracis strains from outbreaks of disease in Victoria identified the presence of multiple genotypes associated with these outbreaks. The geographical distribution of genotypes within Australia suggests that a single genotype was introduced into the eastern states of Australia, followed by the spread and localised differentiation of the pathogen (MLVA25 genotypes MG1-MG6) throughout the anthrax belt. In contrast, unexplained occurrences of disease in areas outside of this anthrax belt which are associated with different genotypes, (MLVA25 genotypes MG7 and MG8) indicate separate introductions of B. anthracis into Australia.